Design and development of IIUM hovercraft - Syed Mohamed Ali, Jaffar; Muhammad Muhaimin, M.Y.; Muhammad Faizal, C.N (2013)
Hovercrafts are air cushioned vehicles having unique capabilities of hovering and travelling on any surface. A full scale hovercraft prototype has been developed indigenously in international Islamic University Malaysia (IIUM). In this paper the engineering design and development process and challenges faced beginning from the concept to the final product have been discussed in detail. The hovercraft has been tested successfully.